Tissue factor pathways linking obesity and inflammation - Ruf, W.; Samad, F. (Hämostaseologie, 2015)
Obesity is a major cause for a spectrum of metabolic syndrome-related diseases that include insulin resistance, type 2 diabetes, and steatosis of the liver. Inflammation elicited by macrophages and other immune cells contributes to the metabolic abnormalities in obesity. In addition, coagulation activation following tissue factor (TF) upregulation in adipose tissue is frequently found in obese patients and particularly associated with diabetic complications. Genetic and pharmacological evidence indicates that TF makes significant contributions to the development of the metabolic syndrome by signaling through G protein-coupled protease activated receptors (PARs). Adipocyte TF-PAR2 signaling contributes to diet-induced obesity by decreasing metabolism and energy expenditure, whereas hematopoietic TF-PAR2 signaling is a major cause for adipose tissue inflammation, hepatic steatosis and inflammation, as well as insulin resistance. In the liver of mice on a high fat diet, PAR2 signaling increases transcripts of key regulators of gluconeogenesis, lipogenesis and inflammatory cytokines. Increased markers of hepatic gluconeogenesis correlate with decreased activation of AMP-activated protein kinase (AMPK), a known regulator of these pathways and a target for PAR2 signaling. Clinical markers of a TF-induced prothrombotic state may thus indicate a risk in obese patient for developing complications of the metabolic syndrome.
Keywords: TF; PARs